An Analysis of English Teachers’ Challenges in Implementing Merdeka Curriculum at Sman 3 Solok Selatan - Septrida Fitra; Yuli Tiarina (Universitas Negeri Padang, 2023)
This research was done to investigate the challenges faced by English teachers in implementing Merdeka curriculum at SMAN 3Solok Selatan. To find out the answers, researcher used descriptive qualitative method with in-depth interview and documentation instrument were employed in this study. The participants of the study were three English teachers at SMAN 3 Solok Selatan. The result showed that there were five challenges faced by English teachers in implementing Merdeka curriculum. Those five challenges in implementing Merdeka curriculum were designing lesson plan, lesson implementation, using media, classroom management, and learning assessment. Through this research, it is expected the result from this finding can help the English teachers to cover the challenges in implementing Merdeka curriculum.